Causes of death of birds at Slimbridge, 1955-1957 - Jennings, A R (Wildfowl, 1959)
A total of 680 birds has been examined in the period 1955-1957. Routine post-mortem examinations have been carried out and where necessary bacteriological, parasitological and histological examinations have been made. The annual mortality and the causes of death are summarised in Table I. The birds have been assigned to three main age groups; adults, immature and downy young and newly hatched chicks. The numbers of birds do not represent the total mortality at Slimbridge since not all dead birds were examined post-mortem. This is particularly the case in regard to the newly hatched young because, when very large batches of chicks were received at the laboratory, only representative samples were examined.